Предмет: Алгебра,
автор: Reideen
Решите пожалуйста, условие на фото
Приложения:
Ответы
Автор ответа:
0
y=f(x);f(-x)=-f(x)
f(x)=3x-x²;x≥0
f(-√3)-f(-2√3)=-f(√3)-(-f(2√3)=
-f(√3)+f(2√3)=
=-(3*√3-(√3)²)+(3*2√3-(2√3)²)=
-(3√3-3)+(6√3-12)=-3√3+3+6√3-12=
3√3-9
f(x)=3x-x²;x≥0
f(-√3)-f(-2√3)=-f(√3)-(-f(2√3)=
-f(√3)+f(2√3)=
=-(3*√3-(√3)²)+(3*2√3-(2√3)²)=
-(3√3-3)+(6√3-12)=-3√3+3+6√3-12=
3√3-9
Автор ответа:
1
Решение задания приложено. 2 способа.
Приложения:
Похожие вопросы
Предмет: Английский язык,
автор: asylzhanzhanibekkyzy
Предмет: Русский язык,
автор: 89049715720shabanova
Предмет: Геометрия,
автор: chajanastasia558
Предмет: Литература,
автор: elba30
Предмет: История,
автор: Nika13120197